Saatnya Untuk Berinvestasi Di Instrumen Saham Dan Obligasi Sebagai Komoditas Perdagangan Internasional - Fauzi, Teddy Hikmat (Jurnal Administrasi Bisnis, 2010)
The currency of volatility can be influence to financial investment instrument asin global, regional or national economic system. Currency fluctuation can used forfinancial investment recommendation in money market capital market or anotherinvestment for commodity market or real sector.Investment changed moment can give a new expectation for strengthening IDRin our country for fund investation bond and stock trading sector that why nationaleconomic positive signal extend so that in a same time too can give more negativesignal if Indonesian government not seriously an investors guaranteed etc govern-ment life awaken like as democratic, honest, accountable and transparant for nationaleconomic and politics condition and situation.Keywords: volatility, stock and bond market